The wow effect and behavioral intentions of tourists to astrotourism experiences: Mediating effects of satisfaction - Rodrigues, Áurea (2022)
The purpose of this study is to ascertain the effect of awe on tourist behavioral inten- tions for astrotourism destinations. Awe is theorized as a multi-dimensional concept with both cognitive and affective elements. A behavioral model depicting the relation- ships among awe, tourist satisfaction and behavioral intentions is proposed and exam- ined among 304 tourists to the Dark Sky Party Alqueva in Portugal. Using partial-least squares structural equation modeling (PLS-SEM), the results indicate that awe directly affects tourist satisfaction and indirectly affects behavioral intentions when mediated by tourist satisfaction. Theoretical and managerial implications are presented.